2017
DOI: 10.5114/jcb.2017.72547
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of post-implant regional dosimetric parameters at 24 hours and one month, with clinical results of low-dose-rate brachytherapy for localized prostate cancer

Abstract: PurposeTo evaluate the correlations of post-implant regional dosimetrics at 24 hours (24 h) and 1 month after implant procedures, with clinical outcomes of low-dose-rate (LDR) brachytherapy for localized prostate cancer.Material and methodsBetween January 2008 and December 2014, 130 consecutive patients treated for localized prostate cancer, receiving definitive iodine-125 (125I) brachytherapy treatment were retrospectively analyzed. All patients underwent post-implant CT imaging for dosimetric analysis at 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this study, late GU toxicities ≥ grade 2 in the combination therapy group showed a rate of 8.3% and the BT monotherapy group 11.1%. In the previous reports of BT monotherapy, the late GU toxicity rate was 8.1-22.3% [ 17 , 18 ], and late urinary retention was reported in 0.6% [ 4 ]. By contrast, a study of BT and EBRT combination therapy reported a late GU grade 2 toxicity rate of 17% and grade 3 – 3% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, late GU toxicities ≥ grade 2 in the combination therapy group showed a rate of 8.3% and the BT monotherapy group 11.1%. In the previous reports of BT monotherapy, the late GU toxicity rate was 8.1-22.3% [ 17 , 18 ], and late urinary retention was reported in 0.6% [ 4 ]. By contrast, a study of BT and EBRT combination therapy reported a late GU grade 2 toxicity rate of 17% and grade 3 – 3% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been no reports about it in combination therapy vs. BT monotherapy. In BT monotherapy, there has been one report of a late hematuria rate of 15.4% [ 17 ], and several reports of late rectal hemorrhage rates of 6-16% [ 3 , 4 , 17 ]. In our study, only one late grade 1 rectal hemorrhage in the monotherapy group was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Individual risk factors (tumor stages, PSA levels, Gleason scores) however correlated less well with the observed outcomes, and thus appear to be less valuable than prognostic risk groups in the context of brachytherapy, at least in the timeframe of 5 years [ 34 ]. In particular, the tumor stage cT2c (tumor covering both lobes) was not associated with lower 5-year bPFS than cT2a or cT2b (tumor confined to ≤ 50 or > 50% of one lobe, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The prostate volume was divided into four quadrants, such as anterior-superior quadrant (ASQ), posterior-superior quadrant (PSQ), anterior-inferior quadrant (AIQ), and posterior-inferior quadrant (PIQ). The superior- inferior and anterior-posterior segments were divided by the midpoint of the prostate on reconstructed CT images ( Figure 1 ) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, although most previous reports refer to the dosimetric parameters of the whole prostate, some have evaluated dose distribution in different regions of the prostate [ 10 ]. We have previously reported the usefulness of sector analysis for localized prostate cancer treated with LS [ 22 ].…”
Section: Purposementioning
confidence: 99%